Library analytics and metrics using data to drive decisions and services - Showers, Ben (London Facet Publishing, 2015)
This book will inform and inspire librarians, archivists, curators and technologists to make better use of data to help inform decision-making, the development of new services and the improvement of the user experience. With the wealth of data available to library and cultural heritage institutions, analytics are the key to understanding their users and improving the systems and services they offer. Using case studies to provide real-life examples of current developments and services, and packed full of practical advice and guidance for libraries looking to realize the value of their data, this will be an essential guide for librarians and information professionals. Library Analytics and Metrics brings together a group of internationally recognized experts to explore some of the key issues in the exploitation of data analytics and metrics in the library and cultural heritage sectors, including: * The role of data in helping inform collections management and strategy * Approaches to collecting, analyzing and utilizing data * Using analytics to develop new services and improve the user experience * Using ethnographic methodologies to better understand user behaviours * The opportunities of library data as 'big data' * The role of 'small data' in delivering meaningful interventions for users * Practical advice on managing the risks and ethics of data analytics * How analytics can help uncover new types of impact and value for institutions and organizations. Readership: This book will be an invaluable resource for librarians and library directors interested in developing a data-driven approach to their service provision and decision making; students on library and information science courses; and managers and practitioners in other cultural heritage sectors such as museums, archives and galleries.
Introduction : getting the measure of analytics and metrics -- 1. Library data : big and small -- 2. Data- driven collections management -- 3. Using data to demonstrate library impact and value -- 4. Going beyond the numbers : using qualitative research to transform the library user's experience -- 5. Web and social media metrics for the cultural heritage sector -- 6. Understanding and managing the risks of analytics -- 7. Conclusion : towards a data-driven future?
This book will enable libraries to make informed decisions, develop new services and improve user experience by collecting, analysing and utilising data.
Includes bibliographical references and index.
Keywords: Web usage mining; Libraries -- Evaluation; Library statistics; Bibliometrics